Influence of human salivary enzymes on odorant concentration changes occurring in vivo. 1. Esters and thiols - Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2002)
The influence of human whole saliva on odor-active esters and thiols was investigated. Special emphasis was placed on food-relevant concentrations of the odorants. It was found that the amounts of the esters were reduced during incubation with saliva to different extents according to their chemical structures. Considerable degradations were also observed for 2-furfurylthiol, 2-phenylethanethiol, and 3-mercapto-3-methyl-1-butanol, being reduced from similar to70 to 20% of their initial concentrations within a period of 10 min. Decrease of the odorants did not occur after thermal treatment of the saliva. Generally, the enzymic processes were found to be dependent on the salivary activity of each individual panelist as well as on the odorant's concentrations applied. These investigations were aimed at finding an explanation for the persistence of aftertaste in humans, as it is induced by some odor-active compounds after the consumption of food materials.
Keywords: 2-furfurylthiol; 2-phenylethanethiol; 3-mercapto-3-methyl-1-butanol; ethyl butanoate; ethyl hexanoate; ethyl octanoate; aftertaste